Experimental study of linear and nonlinear regimes of density-driven instabilities induced by CO2 dissolution in water - Outeda, Mabel Noemi (2014)
Density driven instabilities produced by CO2 (gas) dissolution in water containing a color indicator were studied in a Hele Shaw cell. The images were analyzed and instability patterns were characterized by mixing zone temporal evolution, dispersion curves, and the growth rate for different CO2 pressures and different color indicator concentrations. The results obtained from an exhaustive analysis of experimental data show that this system has a different behaviour in the linear regime of the instabilities (when the growth rate has a linear dependence with time), from the nonlinear regime at longer times. At short times using a color indicator to see the evolution of the pattern, the images show that the effects of both the color indicator and CO2 pressure are of the same order of magnitude: The growth rates are similar and the wave numbers are in the same range (0?30 cm-1) when the system is unstable. Although in the linear regime the dynamics is affected similarly by the presence of the indicator and CO2 pressure, in the nonlinear regime, the influence of the latter is clearly more pronounced than the effects of the color indicator.